MULLĀ ṢADRĀ'S CRITICISM OF REINCARNATION - Kholid Al Walid (Sekolah Tinggi Agama Islam Sadra, 2023)
The concept of reincarnation is believed to be the rebirth of humans in the world as a form of part of their life journey in accordance with their actions during life with various forms of reincarnation—including being able to be reborn as humans or animals. This article aims to discuss Mullā Ṣadrā’s eschatological thoughts, especially his criticism of the concept of reincarnation which has been believed by Hindus and Buddhists. Reincarnation is a topic of discussion for philosophers including Islamic philosophers in discussing the spirit, soul, body, death, and resurrection. Ṣadrā’s rejection of the concept of reincarnation is found in one of his main works entitled al-Asfār al-Arba‘ah. By using analytical and descriptive methods, it was concluded that Mullā Ṣadrā rejected the concept of reincarnation with his five philosophical arguments, including the natural unity argument, the material and form needs argument, Kawn and Fasād’s argument, the vacuum argument, and the argument with five premises. These philosophical arguments are based on Ṣadrā’s main philosophical principle, namely the substantial movement of the soul. Even though he rejects the concept of reincarnation, Ṣadrā still believes in the resurrection of the soul and body after death, which will continue the journey towards the highest perfection in the afterlife.